Household saving and fiscal policy: Evidence for the euro area from a thick modelling perspective - Cristina Checherita-Westphal; Marcel Stecher (European Central Bank (ECB), 2021)
We study the relationship between fiscal policy and household saving across the euro area countries for the period 1999-2019. To this extent, we propose a thick modelling approach, which allows a vast number of model specifications in a dynamic panel setting. We find that fiscal expansions are associated with an increase in household saving rate in the euro area, which supports a partial, but not full, Ricardian equivalence channel. The relationship holds regardless of how we measure the (discretionary) fiscal policy impulse. The median saving offset across all baseline specifications is around 19% in the short run and 41% in the long run. Various robustness checks underpin the basic results, while also pointing to model and estimation uncertainty and no robust evidence for total private saving offset. Our results for the euro area are broadly in line with the literature, albeit they tend to yield a somewhat weaker evidence for the saving offset of fiscal policy, particularly in relation to earlier studies.
Keywords: D14; E62; H6; 330; household saving; fiscal policy; national budget; deficit and debt